Neutropenic Sepsis in the ICU: Outcome Predictors in a Two-Phase Model and Microbiology Findings - Jan M. Kruse; Thomas Jenning; Sibylle Rademacher; Renate Arnold; Clemens A. Schmitt; Achim Jörres; Philipp Enghard; Michael Oppert (Critical Care Research and Practice)
Objective. Patients with neutropenic sepsis have a poor prognosis. We aimed to identify outcome predictors and generate hypotheses how the care for these patients may be improved. Methods. All 12.352 patients admitted between 2006 and 2011 to the medical ICUs of our tertiary university center were screened for neutropenia; out of 558 patients identified, 102 fulfilled the inclusion criteria and were analyzed. Severity markers and outcome predictors were assessed. Results. The overall ICU mortality was 54.9%. The severity of sepsis and the number of organ failures predicted survival of the primary septic episode (APACHE II 22.8 and 29.0; SOFA 7.3 and 10.1, resp.). In the recovery phase, persistent organ damage and higher persistent C-reactive protein levels were associated with a poor outcome. Blood transfusions and CMV infection correlated with an unfavorable prognosis. Ineffective initial antibiotic therapy, fungal infections, and detection of multiresistant bacteria displayed a particularly poor outcome. Infections with coagulase-negative staphylococci and enterococci were associated with a significantly higher mortality and a high degree of systemic inflammation. Conclusion. Patients with persistent organ dysfunction show an increased mortality in the further course of their ICU stay. Early antimicrobial treatment of Gram-positive cocci may improve the outcome of these patients.